Ocular Hypertension Following Open Globe Injury in Patients Undergoing Pars Plana Vitrectomy - Karimaghaei,Sam; Al-Hindi,Hytham; Chauhan,Muhammad; Elhusseiny,Abdelrahman; Sanvicente,Carina; Uwaydat,Sami (Clinical Ophthalmology, 2025)
Sam Karimaghaei, Hytham Al-Hindi, Muhammad Z Chauhan, Abdelrahman M Elhusseiny, Carina T Sanvicente, Sami H Uwaydat Harvey and Bernice Jones Eye Institute, Department of Ophthalmology, University of Arkansas for Medical Sciences, Little Rock, AR, USACorrespondence: Sami H Uwaydat, Department of Ophthalmology, Jones Eye Institute, University of Arkansas for Medical Sciences, 4301 W Markham Street # 523, Little Rock, AR, 72205, USA, Email SHUwaydat@uams.eduPurpose: To identify risk factors and rates of post-traumatic ocular hypertension (OHT) in patients undergoing pars plana vitrectomy (PPV) for open-globe injuries.Patients and Methods: Retrospective chart study including 98 eyes from 98 patients between 2008 and 2022 with open globe injuries who were hospitalized at a single academic institution and received first repair or exploration followed by PPV. Variables recorded included timing to the first PPV, best-corrected final visual acuity (VA) at the last follow-up, incidence of enucleation, type of injury, use of intravitreal antibiotics, number of eye surgeries, use of oral steroids, acetazolamide use, topical steroid use, lens status, silicone oil placement, and zone of injury (1â€“ 3). The ocular trauma score (OTS) was calculated using the variables globe rupture, development of endophthalmitis, initial VA, globe perforation, retinal detachment, and the presence of a relative afferent pupillary defect (RAPD). The primary endpoint was elevated intraocular pressure (IOP) sustained for more than six weeks following PPV. We performed a logistic regression to determine the factors that predicted the development of OHT post-PPV.Results: Of 98 eyes included in the primary analysis, a total of 34 (34.69%) were diagnosed with sustained ocular hypertension (OHT) and 64 (65.31%) remained normotensive. The mean final IOP in the OHT group was 16.96Â mmHg and 12.11Â mmHg in the normotensive group (P < 0.01). Sex, age, OTS, injury type, zone of injury, preoperative IOP, and final VA were comparable between ...